Pasar sebagai Ruang Sosial-kultural dan Terapi Simbolik: Studi tentang Pasar Jum’at Pahing di Desa Arjosari - Hidayah, Miftahul; Malik, Parhan Abdul; Eirelina, Farah; Khoir, Nurus Shobahul; Maulidiarsyah, Faruq Faroiz; Hazimi, Bahrevy Ahmad Nur; Saputra, ⁠Lubbul Hikam; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2026)
This study explores the multidimensional role of the Jum’at Pahing Market in Arjosari Village as a socio-cultural space that integrates economic activities with local healing rituals. Using a qualitative approach with interviews, the research finds that the market serves as an instrument for the social reintegration of individuals with mental disorders. The practice of bringing the sick to the market on specific market days is not merely a commercial transaction but a symbolic act of releasing illness through inclusive interactions that reduce social stigma. The findings indicate that the crowded atmosphere and community acceptance within the market generate positive psychological stimulation that supports the subjective improvement of the patient’s condition. The study concludes that this phenomenon is a cultural mechanism within the framework of medical pluralism that strengthens social cohesion and local wisdom in rural mental health management.